Analysis of the Validity of Authentic Deeds and Legal Responsibility of Notaries in Land Mafia Cases - Momos Endrico; Tjempaka Tjempaka (PT Publikasiku Academic Solution, 2023)
The judgment of the court in the case of mafia land where the notary/ppat proved to commit acts against the law is the background of this research, the purpose of this study to know the validity of the authentic acts made and the legal responsibility of the Notary /ppat who proved to be involved in the mafia case. This research is a normative jurisprudence or research, The approach used is the approach of laws (statue approach) and the case approach. (Case approach). The type of data in this study is secondary data, i.e. data obtained from empirical materials. Analysis of data in this study using the qualitative method of validation of authentic acts canceled by law because there are and proved elements of counterfeiting, lies and fraud, It is regulated in Article 1321 BW that there is no valid agreement when the agreement is given due to misconduct, or obtained by coercion or fraud. Notaries who are involved in the creation of authentic acts that falsify the truth are fully liable for the legal consequences of the approval of the authentical acts made by notaries using the authority to sell false acts not in accordance with the elements of the legal power will be canceled by law, according to Article 1321 BW. The notary/ppat in the case of land mafia with the victim of nirina zubir is an act without questioning the mistake in manipulating authentic acts, which means remaining responsible with criminal punishment.